Pelatihan Pembuatan Yogurt Kacang Merah Pada Siswa SMK di Yogyakarta - Wahyuningsih, Siti; Putriningtyas, Natalia Desy; Iyyah, Isra (Jurnal Pengabdian Dharma Bakti, 2019)
Teenager is a transition period that characterized by changes in physical, psychological and physosocial aspects. The vocational field is one of the learning choices that seeks to empower adolescents, especially at the high school level. Entrepreneurship is an activity that is already familiar in Indonesia. One of the main problems of entrepreneurship in Indonesia is the uneven understanding of the importance of entrepreneurship in supporting the country’s economic progress. The spirit of entrepreneurship is also needed so as to reduce the number of unemployed. The purpose of this activity to increase knowledge on how to process kidney beans while providing information along with solutions to entrepreneurship at the level of high school students. The methods was done through the provision of materialon the procedures for making kidney beans yogurt and this benefits for health, questions and answers with accompanying explanations of tools and materials and showing the results of kidney beans yogurt products. The target of the implementation was the Bopkri Vocational School students in Yogyakarta city and students of SMK Ma’arif 2 Sleman on the suburban Yogyakarta. The training was held from March- November 2018. The results showed that the achievement of pre test and post test was an increase in student’s knowledge about the making of kidney bean yoghurt and the benefits for health.Keywords: The training, yogurt, kidney bean, student of SMK